Measurement of exclusive Upsilon photoproduction from protons in pPb collisions at root sNN=5.02 Tev - Sirunyan, A. M. (2019)
The exclusive photoproduction of (nS) meson states from protons, (nS) p (with n = 1, 2, 3), is studied in ultraperipheral pPb collisions at a centre-of-mass energy per nucleon pair of The measurement is performed using the decay mode, with data collected by the CMS experiment corresponding to an integrated luminosity of 32.6 nb(-1). Differential cross sections as functions of the nS) transverse momentum squared and rapidity y, are presented. The 1S) photoproduction cross section is extracted in the rapidity range < 2.2, which corresponds to photon-proton centre-of-mass energies in the range 91 W < 826 GeV. The data are compared to theoretical predictions based on perturbative quantum chromodynamics and to previous measurements.